2019
DOI: 10.1111/phen.12282
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial insects and climate change: adaptive responses in key traits

Abstract: Understanding and predicting how adaptation will contribute to species' resilience to climate change will be paramount to successfully managing biodiversity for conservation, agriculture, and human health‐related purposes. Making predictions that capture how species will respond to climate change requires an understanding of how key traits and environmental drivers interact to shape fitness in a changing world. Current trait‐based models suggest that low‐ to mid‐latitude populations will be most at risk, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 199 publications
(327 reference statements)
4
109
0
Order By: Relevance
“…Current evidence suggests that plastic responses of insects to heat are limited and may not be sufficient to withstand ongoing warming trends (Gunderson & Stillman, ; Kellermann & Sgrò, ). Furthermore, although important for rapid responses to sudden climate changes, plasticity has not yet been linked to sustained responses with fitness benefits across generations in insects (Kellermann & van Heerwaarden, ; Radchuk et al ., ). In fact, plasticity could even hinder adaptive responses to climate change, as shown for the butterfly Bicyclus anynana , where seasonal plasticity is related to gene expression variation instead of intra‐population genetic variation for plasticity, thus limiting the potential for adaptive responses (Oostra et al ., ).…”
Section: Coping With High Temperatures: Plastic and Evolutionary Respmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests that plastic responses of insects to heat are limited and may not be sufficient to withstand ongoing warming trends (Gunderson & Stillman, ; Kellermann & Sgrò, ). Furthermore, although important for rapid responses to sudden climate changes, plasticity has not yet been linked to sustained responses with fitness benefits across generations in insects (Kellermann & van Heerwaarden, ; Radchuk et al ., ). In fact, plasticity could even hinder adaptive responses to climate change, as shown for the butterfly Bicyclus anynana , where seasonal plasticity is related to gene expression variation instead of intra‐population genetic variation for plasticity, thus limiting the potential for adaptive responses (Oostra et al ., ).…”
Section: Coping With High Temperatures: Plastic and Evolutionary Respmentioning
confidence: 99%
“…However, when temperature was experimentally increased at a rate of 0.3°C per generation, D. melanogaster heat tolerance did not increase even after 20 generations, indicating low evolutionary potential in this trait (Schou et al ., ). Indeed, selection plateaus for heat tolerance have often been described for D. melanogaster (Kellermann & van Heerwaarden, ) and comparative evidence across the genus Drosophila suggests that adaptation to heat is actually slow and has little potential to protect species that already live close to their upper thermal limits (Sørensen et al ., ). Also, it is important to note that, given their dependence on factors specific to the considered populations (e.g.…”
Section: Coping With High Temperatures: Plastic and Evolutionary Respmentioning
confidence: 99%
“…Nevertheless, considering results from the studies in Table 1 along with spatial or occupancy surveys (e.g., 18), conclusions do emerge. Ongoing climate change will have positive effects on some species and negative effects on others (54, 55), with the balance (of positive and negative effects) determined in some cases by geographic factors such as latitudinal position (20, 37) and in other cases by more complex species-specific traits (6, 7), as in the Northern California case study (Fig. 2).…”
Section: Conclusion and Practical Lessonsmentioning
confidence: 99%
“…Similarly, species from stable environments are predicted to have a lower thermal acclimation capacity than those from more variable habitats (e.g., Feder, ; Markle & Kozak, ; Shah, Funk, & Ghalambor, ; Tomanek, and references herein). As an extreme example, some Antarctic cold‐stenothermal species (e.g., Clark, Fraser, Burns, & Peck, ; Clark Fraser & Peck, ; La Terza, Papa, Miceli, & Luporini, ; Rinehart et al, ; Somero, ) as well as warm stenothermal coral reef fishes (Kassahn et al, ; Nilsson, Östlund‐Nilsson, & Munday, ) have lost the ability to activate a heat shock response via the expression of heat shock proteins, which makes them especially vulnerable to global change (Kellermann & van Heerwaarden, ; Patarnello, Verde, Prisco, Bargelloni, & Zane, ; Somero, ). These questions remain poorly explored in other extremely thermally stable habitats, such as subterranean environments, although some recent studies have found support for the climatic variability hypotheses for cave springtails (Raschmanová, Šustr, Kováč, Parimuchová, & Devetter, ) and spiders (Mammola, Piano, Malard, Vernon, & Isaia, ).…”
Section: Introductionmentioning
confidence: 99%